2005
DOI: 10.1016/j.ijinfomgt.2005.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Student use of electronic information services in further education

Abstract: Urquhart,C., Thomas, R., Spink, S., Fenton, R., Yeoman, A., Lonsdale, R., Armstrong, C., Banwell, L., Ray, K., Coulson, G. & Rowley, J. (2005). Student use of electronic information services in further education. International Journal of Information Management, 25(4), 347-362. Sponsorship: JISCThis paper presents a profile of user behaviour in relation to the use of electronic information services (EIS), information skills, and the role of training and wider learning experiences in UK further education col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 1 publication
2
21
0
Order By: Relevance
“…The present study confirmed the results of a previous study about discipline and information seeking behavior among Greek graduate students of the Aristotle University of Thessaloniki (Korobili et al, 2011). In both studies it was found that the information seeking behavior of respondents seemed not to be affected by their discipline, which is in agreement with some earlier studies (Ellis et al, 1993;Heinström, 2003;Sharifabadi, 1996) but contrary to some other significant studies reported in the literature (George et al, 2006;Kerins et al, 2004;Makani & WooShue, 2006;Sadler & Given, 2007;Nicholas et al, 2009;Talja & Maula, 2003;Urquhart et al, 2005;Whitmire, 2002). However, in this study statistically significant relationships were found between disciplines and students' preferences for initiating a search for relevant information.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present study confirmed the results of a previous study about discipline and information seeking behavior among Greek graduate students of the Aristotle University of Thessaloniki (Korobili et al, 2011). In both studies it was found that the information seeking behavior of respondents seemed not to be affected by their discipline, which is in agreement with some earlier studies (Ellis et al, 1993;Heinström, 2003;Sharifabadi, 1996) but contrary to some other significant studies reported in the literature (George et al, 2006;Kerins et al, 2004;Makani & WooShue, 2006;Sadler & Given, 2007;Nicholas et al, 2009;Talja & Maula, 2003;Urquhart et al, 2005;Whitmire, 2002). However, in this study statistically significant relationships were found between disciplines and students' preferences for initiating a search for relevant information.…”
Section: Discussionsupporting
confidence: 91%
“…In relation to cognitive processes and the academic environment, some studies have found that discipline plays a significant role in information seeking (George et al, 2006;Kerins et al, 2004;Makani & WooShue, 2006;Nicholas, Clark, Rowlands, & Jamali, 2009;Whitmire, 2002;Sadler & Given, 2007;Talja & Maula, 2003;Urquhart et al, 2005), while others have noticed the existence of significant variations between different institutions (Nicholas, Huntington, & Jamali, 2007;Nicholas et al, 2009) due to different "faculty models of research behavior" (Barrett, 2005). However, a number of studies also found little or no correlation between discipline and information seeking behavior (Ellis, Cox, & Hall, 1993;Heinström, 2003;Korobili, Malliari, & Zapounidou, 2011;Sharifabadi, 1996).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many studies consider that discipline plays a vital role in information-seeking behavior. [3][4][5] Specifically, Sadler & Given 6 found that there were differences in the attitudes of social sciences graduate students toward e-journals versus their peers in the sciences and engineering. While Rowlands & Nicholas 7 found accumulated evidence of domain differences in information behavior.…”
Section: Review Of Literaturementioning
confidence: 99%
“…[76][77][78][79][80][81][82][83] Searching databases or e-journals was not as popular as search engines. [84][85][86][87] The greatest percentage of graduate students in the study, regardless of their discipline, had more than 5 years of experience in using computers and the Internet and less than 5 years of experience in using databases and ejournals. Accordingly, most respondents perceived themselves as very experienced in retrieving information from search engines.…”
Section: Clusters According To Information-seeking Behaviormentioning
confidence: 99%
“…This trend was confirmed by the results of a survey carried in 2001-2003 on further education (FE) colleges in UK, which showed that FE students do not use OPACs as much as they use other sources of information such as Internet search engines or organisational websites. Therefore researchers are eager to assess user satisfaction with library services and for this they have used both qualitative and quantitativeled studies to measure user levels of satisfaction with library services [24]. Moreover, as library managers are enthusiastic to know what differences their library services make to Learning, Teaching and Research (LTR), there have been an increasing number of studies on different approaches and methods for measuring the impact of these services on academic life [19,7].…”
Section: Introductionmentioning
confidence: 99%